LIVABILITY CONCEPT IN RUMAH SEDERHANA SEHAT BY PROCUREMENT OF INFRASTRUCTURE, FACILITIES, AND UTILITY IN KABUPATEN SIDOARJO - Kartika Dwi Paramitha; Ispurwono Soemarno; Johan Silas (Journal of Architecture&ENVIRONMENT, 2012)
Rumah Sederhana Sehat means adequate and affordable homes in safe and healthy environment. Its presence must be supported by public infrastructures, facilities, and utilities in sustainable manner. This study aims to ensure that the provision of infra-structures, facilities, and utilities in housing not only creates the housing feasibility, but also livability. Kabupaten Sidoarjo is selected as study sites, because it has not had regulations regarding the provision of infrastructures, facilities, and utilities in the housing yet. This study uses a livable city theoretical approach as the main refe-rence. The study is a qualitative study, with post-positivist approach that used to assess the object of this study not only the empirical facts, but also the social life that occur within it. The method of this study is comparison case studies method. It is used to find the influence of housing and infrastructures, facilities, and utilities physical condition towards resident’s psychological condition. The approach to the livable theory covers all aspects of the housing towards sustainable living. The results of this study are the livability concept of infrastructures, facilities, and utilities provision in adequate housing. Feasibility of infrastructures, facilities, and utilities on housing is not only making better neighborhoods, but also the welfare of the residents.